Analisis Kesalahan Ejaan Dan Faktor Penyebab Pada Teks Deskripsi Siswa Kelas IX SMP - Anita Rosiana Safitri (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2025)
Spelling errors are one of the main problems that are often found in the writing skills of junior high school students, so analysis is needed to understand the types of errors and the factors that cause them. This study is a qualitative descriptive research that aims to identify the types of spelling errors contained in the description text of students and analyze the causative factors in the description text of grade IX students in one of the junior high schools in Kartasura. The research data is in the form of 29 student description texts. Data collection techniques include reading the text repeatedly, understanding the meaning of each sentence, recording the findings of errors in the sentence, classifying the types of errors, and recapitulating the number of spelling errors found. The results showed that there were 200 spelling errors divided into five main categories: capital letters (45%), punctuation (26%), prepositions (11%), abbreviations (10%), and rewords (8%). The most mistakes occur in capital letters and punctuation. Factors that cause errors include a lack of understanding of PUEBI rules, the influence of informal language, and a lack of writing practice. Based on the findings, it is hoped that teachers can use more effective learning strategies and provide constructive feedback to improve students' understanding and writing skills according to Indonesian rules.